The Effect of Teacher Morale on Student Achievement in an Urban Denominational Elementary School - Phillip-Regis, Lou Anne (My University, 2013)
This study sought to determine whether teacher morale affected the standard of academic achievement at an urban denominational primary school in Trinidad and Tobago. Data were collected from 10 teachers through a questionnaire, as well as from the Secondary Entrance Assessment (SEA) examination scores at both the school and national level. Findings indicated that: 1) there was a low level of achievement at the school, 2) teacher morale was moderately positive, and 3) there was a weak positive correlation between teacher morale and student achievement, suggesting that high teacher morale would lead to high student achievement and vice versa.
Keywords: Primary school teachers; Academic achievement; Urban schools; Teacher attitudes; Denominational schools; Case studies; Trinidad and Tobago